Effect of different sources of water on water quality and growth performance of growing bull (Bangladesh Journal of Animal Science, 2019)
The experiment was conducted to investigate the effect of different sources of water on feed intake and growth performance of growing bull. For this study, sixteen indigenous bulls (Bos indicus), around two years age (132.5±20.5 kg of LW), were divided into four groups having four animals in each treatment group. The animals were supplied with four different sources of water viz. Deep Tube Well Water (DTW =T1), Supply Water from reserve tank (SW = T2), Pond water (PW = T3) and River water (RW = T4). All the animals were fed German Grass (Echinochloa polystachya L.) and concentrate mixture. All the animals were free access to water. Live weight was recorded initially and week interval till end of the feeding trial (12 weeks). The results revealed that animal belonging T1 treatment group showed best growth performance was better in comparison to other treatment groups. Dry matter intake (DMI) was highest for T1 group (3.08 ± 0.08 kg/d) and lowest for T4 group (2.81 ± 0.18 kg/d). The digestible nitrogen free extract (DNFE) and total digestible nutrient (TDN) were higher (P